The Effect of Mechanical Combined Contact Stress with Buckling Load on the Stress Distribution in the Ball and Socket Joint Mechanism - AL Shamaa, Fathi; Salman, Fatima (Al-Khwarizmi Engineering Journal, 2010)
The design of components subjected to contact stress as local compressive stress is important in engineering application especially in ball and socket Joining.  Two kinds of contact stress are introduced in the ball and socket joint, the first is from normal contact while the other is from sliding contact. Although joining two long links (drive shaft in steering cars) will cause the effect of flexural and tensional buckling stress in hollow columns through the ball and socket ends on the failure condition of the joining mechanism. In this paper the consideration of the combined effect of buckling Load and contact stress on the ball and socket joints have been taken, epically on the stress distribution in the contact area. Different parameters have been taken in the design of joint. This is done by changing the angles for applied loads with the principle axis, the angle of contact between ball and socket and using different applied loads.      The problem has been solved using analytical solution for computing the critical loads and using these loads for calculating the stress distribution with finite element method using ANSYS 10. The numerical results have been compared with the experimental method using photo elasticity pattern which shows good agreement between experimental and simulation results.